Extensive Fusion of Mitochondria in Spinal Cord Motor Neurons - Owens, Geoffrey C.; Walcott, Elisabeth C. (PLOS ONE, 2012)
The relative roles played by trafficking, fission and fusion in the dynamics of mitochondria in neurons have not been fully elucidated. In the present study, a slow widespread redistribution of mitochondria within cultured spinal cord motor neurons was observed as a result of extensive organelle fusion. Mitochondria were labeled with a photoconvertible fluorescent protein (mitoKaede) that is red-shifted following brief irradiation with blue light. The behavior of these selectively labeled mitochondria was followed by live fluorescence imaging. Marking mitochondria within the cell soma revealed a complete mixing, within 18 hours, of these organelles with mitochondria coming from the surrounding neurites. Fusion of juxtaposed mitochondria was directly observed in neuritic processes at least 200 microns from the cell body. Within 24 hours, photoconverted mitoKaede was dispersed to all of the mitochondria in the portion of neurite under observation. When time lapse imaging over minutes was combined with long-term observation of marked mitochondria, moving organelles that traversed the field of view did not initially contain photoconverted protein, but after several hours organelles in motion contained both fluorescent proteins, coincident with widespread fusion of all of the mitochondria within the length of neurite under observation. These observations suggest that there is a widespread exchange of mitochondrial components throughout a neuron as a result of organelle fusion.